2023
DOI: 10.1021/acs.inorgchem.3c02057
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Dimensional Hybrid Lead Bromide Ferroelectric Semiconductor with an Out-of-Plane Polarization

Abstract: A two-dimensional (2D) organic−inorganic hybrid perovskite (OIHP) material with out-of-plane ferroelectricity is the key to the miniaturization of vertical-sandwich-type ferroelectric optoelectronic devices. However, 2D OIHP ferroelectrics with out-of-plane polarization are still scarce, and effective design strategies are lacking. Herein, we report a novel 2D Dion−Jacobson perovskite ferroelectric semiconductor synthesized by a rigid-to-flexible cationic tailoring strategy, achieving an out-of-plane polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…There is significant absorption in the ultraviolet region, and the edge of the band extends into the visible light region near 600 nm. Based on the Kubelka–Munk equation, 43,44 the optical bandgap value is estimated to be 2.13 eV (Fig. 3a), which is smaller than the bandgap of common 2D lead iodide semiconductor materials, 45 and is comparable to that of chiral quasi-2D lead iodide hybrid ( R / S -MPA) 2 (MA)Pb 2 I 7 (MA = methylammonium, MPA = methylphenethylammonium) (∼2.08 eV).…”
Section: Resultsmentioning
confidence: 90%
“…There is significant absorption in the ultraviolet region, and the edge of the band extends into the visible light region near 600 nm. Based on the Kubelka–Munk equation, 43,44 the optical bandgap value is estimated to be 2.13 eV (Fig. 3a), which is smaller than the bandgap of common 2D lead iodide semiconductor materials, 45 and is comparable to that of chiral quasi-2D lead iodide hybrid ( R / S -MPA) 2 (MA)Pb 2 I 7 (MA = methylammonium, MPA = methylphenethylammonium) (∼2.08 eV).…”
Section: Resultsmentioning
confidence: 90%
“…Organic–inorganic hybrid perovskite (OIHPs) materials have wide potential applications in intelligent device fields such as information storage, shape memory, actuators, and X-ray radiation detection, etc. On account of they behave the features of an easy synthesis process, tunable structure, and excellent performance. To date, OIHPs have become a good platform to develop a large family of functional materials, such as ferroelectrics, piezoelectrics, ferroelastics, and photoelectric detectors, etc. Similar to ferroelectricity and ferromagnetism, the nonlinear force hysteresis loop characteristic of the inherent spontaneous strain by mechanical force is defined as ferroelasticity. , The response of spontaneous strain orientation to force, light, and thermal stimuli provides potential applications of ferroelastics in mechanical switches, optical domain wall memories, pressure sensors, etc. Notably, recent studies have shown that the ferroelastic domain walls of OIHPs contributing to microscopic carrier transport. ,, Therefore, the introduction of ferroelasticity into semiconductor materials may help to enhance the photoelectric detection property. However, 2D OIHPs ferroelastic crystals with an X-ray radiation current response have hardly been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional metal halide perovskites (2D MHPs) have sparked significant research interest owing to their promising practical applications such as photovoltaics, light-emitting diodes, laser devices, ferroelectrics, and multiferroics . However, melting behaviors of 2D MHPs have received relatively scant attention.…”
Section: Introductionmentioning
confidence: 99%